Smallholder Farmers Spend Credit Primarily on Food: Gender Differences and Food Security Implications in a Changing Climate - Carranza, Marissa; Niles, Meredith T. (Frontiers in Sustainable Food Systems, 2019)
In many low-income nations agriculture is used as the primary source of income, which in the face of a changing climate, is known to be at considerable risk for the smallholder farmers that rely on it. Financial resources may enable smallholder farmers to implement adaptation practices and diversify income and investments, which has the potential to affect household income and food security. Here we explore relationships between access to different types of financial resources among male and female-headed households and women versus men, use of financial resources, and its relationship to food security. We use data from the CGIAR Climate Change, Agriculture, and Food Security (CCAFS) program from four sites including Nyando (Western Kenya) and Wote (Eastern Kenya), Rakai (Uganda) and Kaffrine (Senegal), to represent major farming systems and agro-ecological zones across Africa. We find that male and female-headed households do not attempt to borrow financial resources in significantly different quantities; however, female-headed households are likely to have access to financial resources if they wanted them. We find that men and male-headed households are more likely to access formal loans. As well, we find that male and female-headed households spend their financial resources differently with female-headed households most likely to use their credit for food, medical expenses and education and male-headed households most likely to use it on food, agriculture/ livestock inputs and education. Formals loans were more frequently associated with credit spent on agriculture/livestock inputs while informal loans were more likely to be utilized for buying food and medical care. We find that all households and sexes that attempted to borrow money were less likely to borrow food and other goods, but that female-headed households were more than twice as likely to borrow food overall. These results add nuance to the relationship of financial resources to food security, suggesting that for many smallholders, especially women, credit is often used to obtain food and other health outcomes as compared to on-farm investment. The use of financial resources for these varying purposes likely has different short-term versus long-term returns and tradeoffs, which could influence smallholder farmer capacity for climate change adaptation.